European guideline for the diagnosis and treatment of insomnia. (5th September 2017) - Riemann, Dieter; Baglioni, Chiara; Bassetti, Claudio; Bjorvatn, Bjørn; Dolenc Groselj, Leja; Ellis, Jason G.; Espie, Colin A.; Garcia‐Borreguero, Diego; Gjerstad, Michaela; Gonçalves, Marta; Hertenstein, Elisabeth; Jansson‐Fröjmark, Markus; et al.
Summary: This European guideline for the diagnosis and treatment of insomnia was developed by a task force of the European Sleep Research Society, with the aim of providing clinical recommendations for the management of adult patients with insomnia. The guideline is based on a systematic review of relevant meta‐analyses published till June 2016. The target audience for this guideline includes all clinicians involved in the management of insomnia, and the target patient population includes adults with chronic insomnia disorder. The GRADE (Grading of Recommendations Assessment, Development and Evaluation) system was used to grade the evidence and guide recommendations. The diagnostic procedure for insomnia, and its co‐morbidities, should include a clinical interview consisting of a sleep history (sleep habits, sleep environment, work schedules, circadian factors), the use of sleep questionnaires and sleep diaries, questions about somatic and mental health, a physical examination and additional measures if indicated (i.e. blood tests, electrocardiogram, electroencephalogram; strong recommendation, moderate‐ to high‐quality evidence). Polysomnography can be used to evaluate other sleep disorders if suspected (i.e. periodic limb movement disorder, sleep‐related breathing disorders), in treatment‐resistant insomnia, for professional at‐risk populations and when substantial sleep state misperception is suspected (strong recommendation, high‐quality evidence). Cognitive behavioural therapy for insomnia is recommended as the first‐line treatment for chronic insomnia in adults of any age (strong recommendation, high‐quality evidence). A pharmacological intervention can be offered if cognitive behavioural therapy for insomnia is not sufficiently effective or not available. Benzodiazepines, benzodiazepine receptor agonists and some antidepressants are effective in the short‐term treatment of insomnia (≤4 weeks; weak recommendation, moderate‐quality evidence). Antihistamines, antipsychotics, melatonin and phytotherapeutics are not recommended for insomnia treatment (strong to weak recommendations, low‐ to very‐low‐quality evidence). Light therapy and exercise need to be further evaluated to judge their usefulness in the treatment of insomnia (weak recommendation, low‐quality evidence). Complementary and alternative treatments (e.g. homeopathy, acupuncture) are not recommended for insomnia treatment (weak recommendation, very‐low‐quality evidence).